Analisis Penerapan Perlakuan Akuntansi Akad Murabahah Pada Laboratorium Ekonomi Islam Fakultas Ekonomi Dan Bisnis Universitas Brawijaya - Virginia Nur Rahmanti; Hanifah Aulia Muntolib (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2024)
This study aims to evaluate the murabahah contract transactions learning by analyzing the conformity of the accounting treatment for murabahah financing transactions in the Ekis Lab to PSAK No. 102. This study employs qualitative descriptive method involving data obtained through interviews with the general chairman of the Ekis Lab, 2 members from the financing division, 1 member from the savings division, and 1 member from the Student Executive finance bureau. The results of the study exhibit that some recordings of murabahah contract financing in the Ekis Lab conform to PSAK No. 102, including the recognition and measurement of murabahah assets; recognition, measurement and presentation of murabahah receivables; and margin presentation of murabahah receivables. Whilst, some of which do not conform to PSAK No. 102, including the recognition of murabahah margins, and disclosure of murabahah contract transactions at the Ekis Lab for, respectively, not using amortization to calculate the murabahah margin recognition and the absence of financial statements such as income statements and statements of financial position leading to the absence of the disclosure of several accounts. As such the financial statements must incorporate disclosures of murabahah receivables account disclosed in the statement of financial position, and murabahah receivable margin disclosure account disclosed in the income statement.